Community action for conservation : mexican experiences - Ruiz-Mallén, Isabel; Camacho-Benavides, Claudia; McCandless, Susannah R.; Porter-Bolland, Luciana (Springer New York, 2013)
This book provides an in-depth analysis on community conservation in Mexico. The volume explores vivid examples and case studies that illustrate some of the critical issues at stake, including the participation of local communities in national and global conservation, indigenous and local perceptions of conservation initiatives in Southern Mexico, and challenges in ICCA governance and ecotourism. The book also reviews methodological approaches for understanding and strengthening community conservation, touching upon such topics as community-based biodiversity monitoring and tools for understanding children's perceptions of community conservation. Written by international experts in the field, Community Action for Conservation: Mexican Experiences is a lively and deep-running resource that offers invaluable stories and analyses of the Mexican experience with conservation.